Timer based algorithm for minimum connected dominating set construction - Yang, Yang; Rui, Lan-Lan; Guo, Shao-Yong; Qiu, Xue-Song; Qi, Feng (Tongxin Xuebao, 2013)
In clustered MANET, a timer theory based MCDS algorithm was proposed to construct and reconstruct visual backbone quickly under dynamic topologies. The validity of this MCDS algorithm was established. The simulation results demonstrate that our algorithm produces a CDS of competitive size with low message overhead and adjusts the visual backbone fast to adapt to dynamic network topologies.